The Use of âGoogle Docsâ in Teaching Writing: An Alternative Way of Collaboration in Writing - Ana Setyandari, Umi Sholihah dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This article describes one of innovative strategies for education in digital era. It isbased on the research of utilizing âGoogle Docsâ in teaching writing. Starting fromthe questionnaire and observation that had been done by the researcher to Englishstudents of Widya Dharma University of Klaten in preliminary research, there arestill many students that have low ability in writing because insufficient practice inwriting. Most of writing activities in the class give the theories of writing with lesspracticing. Even when the students did the task, they only did the task based on theinstruction then submitted without any revision. Some students said that sometimesthe lecturer gave correction in class but it consumed the time and not all studentsgot their correction because limited time. When the correction given in othermeeting, it wastes the time and there is no time for making revision. This researchis aimed to face those problems by using âGoogle Docsâ. The using of âGoogleDocsâ gives the opportunities for the students to review othersâ works everywhereand whenever they want, not only in the class. The findings of the research showthat there are significant improvements of studentsâ writing skill after applyingcollaborative learning using âgoogle docsâ. So, it is proven that utilizing âGoogleDocsâ in reviewing studentsâ work can be alternative method to improve writingability.Keywords: writing skill; collaborative learning; google docs; classroom action research